Fiscal Expenditures and Unemployment: A DSGE Perspective - Eric Mayer; Stéphane Moyen; Nikolai Stähler (Verein für Socialpolitik, 2010)
We investigate the behavior of the unemployment rate after a government expenditure shock and present evidence that the group of asset-holding households reacts very different from the group of liquidity-constrained consumers. Our findings suggest that the unemployment rate is likely to decrease for assetholding households while it increases among liquidity-constrained consumers. The main driver for our results is the marginal utility of wealth which moves in opposite directions for the different types of households after a government expenditure shock. We find that the size of the fiscal (unemployment) multiplier increases with i) highly sticky prices ii) high degrees of risk aversion iii) low real wage elasticities iv) high replacement rates and v) debt financed expenditures.
Keywords: E32; E62; H61; 330; search and matching; government shocks; unemployment